The effect of dentin pretreatment using silver nanoparticles on shear bond strength of one self-etch and one etch-and-rinse resin cements - Farzaneh Mohammadi; Fatemeh Koohpeima; Mohammad Javad Mokhtari (Babol University of Medical Sciences, 2022)
Introduction: Metal nanoparticles may apply to the cavity walls as acceptable antibacterial agents. The present work was conducted to assess the effect of silver nanoparticles (NPs) on the resin cements Shear Bond Strength (SBS) using one self-etch and one etch and rinse resin cement. Materials & Methods: Sixty intact noncarious extracted, human third molars were selected. All teeth were cut out in the middle of dentin thickness. Resin cement samples were randomly assigned to five groups: (A) Duolink cement without any further surface treatment; (B) Duolink cement with silver NPs (0.5%) dentin surface treatment after acid etching and before the One Step Plus (OSP) adhesive system; (C) Duolink cement with silver NPs (0.5%) dentin surface treatment before acid etching and OSP; (D) Panavia F2.0 cement without any further surface treatment; and (E) Panavia F2.0 cement with silver NPs (0.5%) dentin surface treatment. SBS was assessed by using universal testing machine. Then, human gingival fibroblasts (HGF) cells were treated with tested materials. The biocompatibility of resin cement was evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. Results: The maximum and minimum of the SBS at the presence of silver NPs were observed in group E (15.81±0.91, P-value<0.01) and group B (12.01±0.15, P-value <0.05), respectively. In comparison with the controls, the resin cements incorporated  with 0, 0.2% and 0.5% silver NPs, 20.34%, 22.00% and 22.67% for Panavia F2.0 and 36.84%, 37.34% and 38.17% for Duolink flow - decreased in total cell number, respectively (P-value<0.01). Conclusion: These findings demonstrated that Panavia F2.0 cement with silver NPs dentin surface treatment showed satisfactory result in the SBS compared to Panavia F2.0 cement without any further surface treatment.